Impact of Yoga on cognition and mental health among elderly: A systematic review. (August 2020) - Chobe, Shivaji; Chobe, Meenakshi; Metri, Kashinath; Patra, Sanjib Kumar; Nagaratna, R
Highlights: The present systematic review included 13 randomized controlled trials. Both cognitive and mental health effects of Yoga are evaluated in the study. Yoga-based intervention have some positie evidence on attention, executive functions and memory among cognitive variables, while depression in mental health parameters compared to active control among the elderly. Present study is preclude about the generalizability of results because of methodological and reporting weaknesses in the included RCTs. Furthermore, randomized controlled trials with robust methodology and long term follow-ups are needed to resolve mixed results and for definitive recommendations. Abstract: Background: Cognitive decline and psychological health problems are the most frequently observed and under-treated issues among the elderly. Many studies have assessed the efficacy of Yoga on cognitive and mental health parameters among the elderly. However, up to date, there is no systematic review done to evaluate the role of Yoga-based interventions on cognition and mental health in the elderly. Objective: This review evaluates the beneficial effect of Yoga in improving cognitive and mental health in the elderly. Methodology: A comprehensive search has performed on Medline, Google Scholar, PubMed, and PsycINFO electronic database from their inception to January 2019. The literature search was constructed around search term for "mental health", "cognition", "yoga" and "elderly". Out of 3388 records, we were considered only Randomized control trials (RCTs) with Yoga-based interventions on the older people for this review. Risk of bias was assessed using Delphi list and PEDro criteria. Results: After filtering out irrelevant studies, in our search, we come across 13 RCTs, and they included in this systematic review. Of 13 RCTs, four studies assessed only cognitive parameters and five studies assessed only psychological parameters, and four studies evaluated both. Study quality was fair to moderate of included RCTs on the Delphi list and PEDro criteria. Maximum studied variables in cognition were executive functions, memory, attention, and language while in mental health depression, anxiety, stress, and mood. Yoga-based interventions have some beneficial effects on attention, executive functions among cognitive variables, and depression among mental health parameters among the elderly. Conclusion: The present review indicates that Yoga-based interventions have some positive evidence in improving attention, executive functions and memory of cognition, while depression in mental health compared to active control among the elderly. However, methodological limitations and small number of studies preclude confirming the potential benefits of Yoga-based interventions on cognition and mental health among the elderly. Further, this review strongly recommends more randomized control trials with standard study methodology, use of validated modules of Yoga intervention, and long term follow up to have definite conclusions.